2017
DOI: 10.1016/j.amsu.2016.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Short-term outcomes after distal pancreatectomy: Laparotomy vs. laparoscopy - A single-center series

Abstract: BackgroundLaparoscopic distal pancreatectomy was introduced 15 years ago, but it is still not widely used. The aim of the study was to compare the postoperative complications and length of stay between open and laparoscopic distal pancreatectomy.Materials and methodsA search of our institutional pancreas database was performed. All consecutive distal pancreatectomy patients from 2000 to 2015 were identified. Demographics, peri- and postoperative outcomes were reviewed. Postoperative complications were graded u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…In total, 2612 studies were identified from the electronic databases, and 954 studies were excluded because they were duplicate publications. Finally, the full texts of 40 studies 11,12,1619,2558 were screened for eligibility; however, 28 studies were excluded for various reasons 11,25,2735,38,39,4143,45–48,5055,57,58 (Supplementary Materials). Only 12 studies 12,1619,26,36,37,40,44,49,56 were included for further analysis.…”
Section: Resultsmentioning
confidence: 99%
“…In total, 2612 studies were identified from the electronic databases, and 954 studies were excluded because they were duplicate publications. Finally, the full texts of 40 studies 11,12,1619,2558 were screened for eligibility; however, 28 studies were excluded for various reasons 11,25,2735,38,39,4143,45–48,5055,57,58 (Supplementary Materials). Only 12 studies 12,1619,26,36,37,40,44,49,56 were included for further analysis.…”
Section: Resultsmentioning
confidence: 99%